Core and Accessory Genome Comparison of Australian and International Strains of O157 Shiga Toxin-Producing Escherichia coli - Pintara, Alexander; Jennison, Amy; Rathnayake, Irani U.; Mellor, Glen; Huygens, Flavia (Frontiers in Microbiology, 2020)
Shiga toxin-producing Escherichia coli (STEC) is a foodborne pathogen, and serotype O157:H7 is typically associated with severe disease. Australian STEC epidemiology differs from many other countries, as severe outbreaks and HUS cases appear to be more often associated with non-O157 serogroups. It is not known why Australian strains of O157 STEC might differ in virulence to international strains. Here we investigate the reduced virulence of Australian strains. Multiple genetic analyses were performed, including SNP-typing, to compare the core genomes of the Australian to the international isolates, and accessory genome analysis to determine any significant differences in gene presence/absence that could be associated with their phenotypic differences in virulence. The most distinct difference between the isolates was the absence of the stx2a gene in all Australian isolates, with few other notable differences observed in the core and accessory genomes of the O157 STEC isolates analysed in this study. The presence of stx1a in most Australian isolates was another notable observation. Since the acquisition of stx2a seems to coincide with the emergence of highly pathogenic STEC, and a lack of other notable genotypic differences was observed between Australian and international isolates including those related to a highly pathogenic outbreak in the UK, this may be further evidence that the absence of stx2a in Australian O157 STEC could be a significant characteristic defining its mild virulence. Further work investigating the driving force(s) behind Stx prophage loss and acquisition is needed to determine if this potential exists in Australian O157 isolates.